Characteristics of sports training accomplished in specific conditions - Garhovac, G.; Guzina, B. (Proceedings of International Scientific Conference Anthropological Aspects of Sports Physical Education and Recreation, 2013)
This research was carried out on a model of first category swimmer, multiple medal winner on regional competitions and owner od State records of Bosnia and Herzegovina. Objective of this research was to determine whether and to what extent staying and training at high altitudes (2300 m) under conditions of hypoxia, affects an increase in number of red blood cells and general qualitative hematological blood examination of examinee for the sake of raising swimmers general level od readiness with desire to achieve higher sport results. Results of t-test indicates an increase in number of erythrocytes (before and after staying on the mountain) for 7%, while hemoglobin and hematocrit remained unchanged. We can conclude that hematological changes, as the most pronaunced physiological adaptation of the organism to hypoxic conditions (training at high altitudes), on effective way increases the capacity of blood to transport oxygen, so thats why its considered as an effective and legal method of blood doping.